2020
DOI: 10.1002/ecy.3108
|View full text |Cite
|
Sign up to set email alerts
|

Warming acts through earlier snowmelt to advance but not extend alpine community flowering

Abstract: Large‐scale warming will alter multiple local climate factors in alpine tundra, yet very few experimental studies examine the combined yet distinct influences of earlier snowmelt, higher temperatures and altered soil moisture on alpine ecosystems. This limits our ability to predict responses to climate change by plant species and communities. To address this gap, we used infrared heaters and manual watering in a fully factorial experiment to determine the relative importance of these climate factors on plant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 83 publications
3
29
0
Order By: Relevance
“…Although this study shows that the phenological response to warming is species-specific, most of the species in this study advanced but not delayed their flowering, a phenomenology that is similar to the findings of other experimental warming studies performed in steppes, prairies, and alpine meadows (Arft et al, 1999;Sherry et al, 2007;Post et al, 2008;Dorji et al, 2013;Jabis et al, 2020). Moreover, other experimental warming studies in the northeast of Tibetan Plateau (Haibei Alpine Meadow) have shown an advance in the onset time of flowering.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although this study shows that the phenological response to warming is species-specific, most of the species in this study advanced but not delayed their flowering, a phenomenology that is similar to the findings of other experimental warming studies performed in steppes, prairies, and alpine meadows (Arft et al, 1999;Sherry et al, 2007;Post et al, 2008;Dorji et al, 2013;Jabis et al, 2020). Moreover, other experimental warming studies in the northeast of Tibetan Plateau (Haibei Alpine Meadow) have shown an advance in the onset time of flowering.…”
Section: Discussionsupporting
confidence: 88%
“…Numerous studies have shown that climate warming affects almost all aspects of biological systems. One of the most extensive studied aspect is plant phenology ( Arft et al, 1999 ; Dunne et al, 2003 ; Sherry et al, 2007 ; Post et al, 2008 ; Dorji et al, 2013 ; Meng et al, 2019 ; Jabis et al, 2020 ), since warming-induced changes in plant phenology may affect species interactions, ecosystem nutrient cycling, and energy flow ( CaraDonna et al, 2014 ). Climate warming is often simulated by manipulative experiments using open top chambers or infrared heaters in different terrestrial biomes ( Marion et al, 1997 ; Arft et al, 1999 ; Sherry et al, 2007 ; Post et al, 2008 ; Dorji et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alpine habitats are highly seasonal and are characterised by a relatively short reproductive period compared to the lowlands at similar latitudes (Nagy and Grabherr, 2009;Lisovski et al, 2017). However, the onset of the reproductive season depends on the timing of snow melt that can be highly variable between years, requiring a level of phenotypic flexibility in organisms to respond accordingly (Martin and Wiebe, 2004;Jabis et al, 2020). Timely arrival at the breeding site is crucial (Møller et al, 2010), and the entire annual schedule of migrants is meticulously tuned and adapted to spring phenology (La Sorte and Graham, 2020), in particular resource availability during offspring rearing (Doiron et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature and snow melt timing are important phenological cues in high‐elevation and high‐latitude plant communities, where climate change is occurring rapidly (Dunne et al, 2003; Høye et al, 2007; Inouye & Wielgolaski, 2013; Jabis et al, 2020; Price & Waser, 1998; Quaglia et al, 2020; Saavedra et al, 2003; Wielgolaski & Inouye, 2013; Wipf & Rixen, 2010; Ziello et al, 2009). Rising temperatures due to climate change are strongly associated with earlier phenology (Forrest & Miller‐Rushing, 2010; Parmesan, 2006; Parmesan & Yohe, 2003; Thackeray et al, 2010).…”
Section: Introductionmentioning
confidence: 99%